Dispersion of thulium-yttria nanoparticles to build up smart structures. (March 2021) - Santos, S.C.; Rodrigues, O.; Campos, L.L
Graphical abstract: Highlights: Zeta potential of Thulium-yttria in aqueous medium is evaluated. Thulium-yttria nanoparticles exhibit mean diameter inferior to 220nm. Thulium-yttria suspensions present isoelectric point between pH 8.5 to pH 9.2. Most thulium-yttria suspensions are highly stabilized at pH 10.5. Stability parameters are useful to form smart materials for dosimetry. Abstract: The development of new materials for radiation dosimetry is a challenge to assure quality improvement practices related to radiation protection concept. On this context, colloidal stability provides conditions to build up smart structured materials from bottom-up perspective. The present work reports zeta potential characterization of thulium-yttria nanoparticles in aqueous medium. Thulium-yttria nanoparticles formed by a relative low temperature hydrotermal synthesis were characterized by XRD, PCS, and SEM. The stability of particles in aqueous medium was evaluated by electrophoretic mobility measurements, followed by zeta potential calculation. The results revealed that the isoelectric point of thulium-yttria suspensions shifted in accordance with thulium concentration from pH 8.5 ("pure" yttria) to pH 9.2 (2at.%Tm). Besides, most suspensions could be stabilized at pH 10.5, presenting zeta potential values around 30 mV. These results are substantial parameters to advance toward new materials for radiation dosimetry.